Delivering 100 Commonwealth Walkways Around the World (breakout presentation). (December 2017) - Walker, Jim
Abstract : The Outdoor Trust, a UK based charity, is working with all 77 Commonwealth Nations and Territories to create permanent, marked walkable routes in 100 main towns and cities to: encourage more people to walk to benefit their health; reduce local congestion; improve air quality and help combat climate change; inspire people to learn more about the richness and diversity of the Commonwealth, and; connect people together (especially young people and indigenous communities). The initiative builds on the success of the Jubilee Walkway in London, the first urban walkway in the world, opened by Her Majesty The Queen in 1977 and connecting central London's main landmarks. A complementary route, The Jubilee Greenway, was commissioned to celebrate The Diamond Jubilee in 2012 connecting the main London 2012 Olympic Games venues and both are now enjoyed by more than 3 million people every year. This presentation will give an overview of the project, the criteria and method for implementing the walkways and future plans for legacy events and outreach work.